Perceptions of Visitors towards the Implementation of Sustainable Tourism at Kawasan Ekowisata Mangrove Wonorejo, Surabaya - Arvin Widiawan; Thomas Santoso; Sienny Thio (Master of Management, School of Business and Management, Petra Christian University, 2020)
The purpose of this study is to determine visitors’ perceptions towards the implementation of sustainable tourism at Kawasan Ekowisata Mangrove Wonorejo (KEMW) as seen from the perspectives of the environmental, economic, as well as social dimensions. The research method used is descriptive quantitative by distributing questionnaires to 101 respondents as KEMW visitors. The study result shows that the implementation of sustainable tourism from the environmental dimension still prioritizes goals that lead to conservation. Sustainable tourism from the economic dimension is directed to provide benefit to the local economy. Whereas from the social dimension, KEMW has given visitors a sense of comfort and security. KEMW management is expected to be able to create more proactive programs, to educate visitors about conservation, and to involve the community to clean up waste in deeper forest areas. Moreover, the management should promote the variety of processed local mangrove products, as well as add facilities that provide easier access for visitors with special needs. Further research can be done by either measuring the level of visitor satisfaction towards the services of KEMW’s employees or identifying the impact of the presence of KEMW on the economic and social characteristics of the local population.